Reduction of Phase and Gain Control Dependencies Within a 20 GHz Beamforming Receiver IC - Yuan Chang; Brian A. Floyd (IEEE Access, 2023)
This paper studies the phase and gain control dependencies of a variable gain amplifier (VGA) and a vector interpolator phase shifter (VIPS) within a 20 GHz beamforming receiver. First, the mechanisms of gain control and phase variation in a classic current-steering VGA are analyzed and design techniques are proposed such that the gain-dependent phase variations (GDPV) introduced by the amplifiers are well balanced. Second, similar analysis is performed to evaluate GDPV within a vector interpolator, where we show how the same techniques only partially apply due to the cross-coupling structure of the interpolator’s VGAs. We evaluate our techniques within a 20 GHz beamforming receiver IC realized in GlobalFoundries 45 nm RFSOI. Very low GDPV is observed within the VGA, with less than 0.3-deg. root-mean squared phase variation for a 9 dB gain control, whereas the VIPS achieves worst-case GDPV of 14 deg. The full beamformer channel achieves 29 dB gain, 2.2-2.4 dB noise figure, −26 dBm input 1 dB compression and consumes 111 mW. Based on these results, improvements to the interpolator are proposed and validated through simulation. The result is a near-ideal Cartesian interpolator that has less than 2-deg. GDPV and very low crosstalk between the VGAs.